Survival and Physiological Recovery after Capture by Hookline: The Case Study of the Blackspot Seabream (Pagellus bogaraveo) - Ignacio Ruiz-Jarabo; Miriam Fernández-Castro; Ismael Jerez-Cepa; Cristina Barragán-Méndez; Montse Pérez; Evaristo Pérez; Juan Gil; Jesús Canoura; Carlos Farias; Juan Miguel Mancera; Ignacio Sobrino (Fishes, 2021)
Evaluating the survival of discarded species is gaining momentum after the new European Common Fisheries Policy (Article 15 of the European Regulation No. 1380/2013). This regulation introduced a discard ban, with an exemption for those species with demonstrated high survival rates after their capture and release. Candidate species should be evaluated for each fishing gear and geographical area. In this study, we assessed not only survival, but also physiological recovery rates of blackspot seabream (Pagellus bogaraveo) below commercial size captured with a hookline called “voracera” in the Strait of Gibraltar (SW Atlantic waters of Europe). Experiments onboard a commercial fishing vessel were paralleled with studies in controlled ground-based facilities, where the capture process was mimicked, and physiological recovery markers were described. Our results confirmed that hookline capture induced acute stress responses in the target species, such as changes in plasma cortisol, lactate, glucose, and osmolality. However, 90.6% of the blackspot seabreams below commercial size captured with this fishing gear managed to survive, and evidenced physiological recovery responses 5 h after capture, with complete homeostatic recovery occurring within the first 24 h. Based on this study, the European Commission approved an exemption from the discard (EU Commission Delegated Regulation 6794/2018). Thus, the robust methodology described herein can be an important tool to mitigate the problem of discards in Europe.